2014
DOI: 10.1177/1534508414560346
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison Between SRSS-IE and SSiS-PSG Scores

Abstract: We report findings of a validation study comparing two screening tools: the Student Risk Screening Scale-Internalizing and Externalizing (SRSS-IE, an adapted version of the Student Risk Screening Scale) and the Social

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…To further explore convergent validity, Lane, Oakes, Common, et al (2015) conducted a convergent validity study comparing SRSS-IE and SSiS-PSG scores with a sample of 458 K-5 students from one school in a southeastern state. Correlation analyses indicated statistically significant inverse relations between SRSS-IE (SRSS-E7 and SRSS-I5 subscale scores and the total score) and SSiS-PSG subscale scores.…”
Section: Psychometric Properties Of the Srss And Srss-iementioning
confidence: 99%
“…To further explore convergent validity, Lane, Oakes, Common, et al (2015) conducted a convergent validity study comparing SRSS-IE and SSiS-PSG scores with a sample of 458 K-5 students from one school in a southeastern state. Correlation analyses indicated statistically significant inverse relations between SRSS-IE (SRSS-E7 and SRSS-I5 subscale scores and the total score) and SSiS-PSG subscale scores.…”
Section: Psychometric Properties Of the Srss And Srss-iementioning
confidence: 99%
“…Glover and Albers (2007) suggested that a good behavioral screener should be efficient (not require too much time) and accurate (psychometrically sound), while also displaying reasonable levels of specificity (can identify exactly what is wrong) and sensitivity (can identify all the children who need help). In addition, all this should exist within the most cost-effective assessment available (Lane et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…BESS psychometric data were obtained from Dever, Mays, Kamphaus, and Dowdy (2012); Kamphaus and Reynolds (2007); and Reynolds and Kamphaus (2004). SSIS-PSG psychometric data were obtained from Gresham and Elliott (2008); Lane et al (2015). Note. PBS = Positive Behavioral Supports; BERS = Behavioral and Emotional Rating Scale: Teacher rating; SSIS-PSG = Social Skills Improvement System: Performance Screening Guide; SSIS = Social Skills Improvement System; SDQ = Strengths and Difficulties Questionnaire; SRSS = Student Risk Screening Scale; SSBD = Systematic Screening for Behavior Disorders; BESS = Behavioral and Emotional Screening Systems. …”
Section: Screeners In Multi-tiered Systemsmentioning
confidence: 99%
See 2 more Smart Citations